2014
DOI: 10.1038/ijir.2014.10
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative erectile function is the only predictor of the use of a high number of phosphodiesterase type-5 inhibitors after bilateral nerve-sparing radical prostatectomy

Abstract: It is well known that the administration of phosphodiesterase type-5 inhibitors (PDE5-Is) may improve erectile function (EF) recovery after bilateral nerve-sparing radical prostatectomy (BNSRP). The aim of our study was to identify predictors of the use of a high number of PDE5-Is (one or more per week) after surgery among 184 patients taking proerectile medications on demand. At a mean follow-up of 22.7 months, 116 patients (63%) recovered EF. Overall, EF recovery rates at 1- and 2- year follow-up were 47.3% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 22 publications
0
3
0
1
Order By: Relevance
“…Patients with ULNS or NonNS are doing far worse; only 10-30% have an acceptable EF [ 4 , 7 , 23 , 24 ]. The (early) penile rehabilitation is more or less exclusively studied in patients with BLNS surgery [ 25 28 ] and its additional value is still under debate and yet to be proven [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Patients with ULNS or NonNS are doing far worse; only 10-30% have an acceptable EF [ 4 , 7 , 23 , 24 ]. The (early) penile rehabilitation is more or less exclusively studied in patients with BLNS surgery [ 25 28 ] and its additional value is still under debate and yet to be proven [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…This choice is not surprising, as PDE5Is are the most straightforward treatment option for ED. However, previous high-quality studies have suggested limited clinical effect in a large proportion of post-RP patients and a lack of effectiveness in terms of rehabilitation [22][23][24]. Therefore, it is concerning that only a few centers offered more lines of rehabilitation with VED, urethral suppositories, and injections.…”
Section: Discussionmentioning
confidence: 99%
“…The likelihood of satisfactory erections after surgery is extremely low in patients with severe ED as measured by IIEF [20,21]. Patients with a higher preoperative IIEF are generally more motivated to achieve satisfactory erectile and sexual function after surgery [22]. Surgical technique and surgeons' experience also have a signi cant impact on the likelihood of ED after surgery [23][24][25][26][27][28][29][30].…”
Section: Discussionmentioning
confidence: 99%